Alexa, Affect, and the Algorithmic Imaginary: Addressing Privacy and Security Concerns Through Emotional Advertising. Issue 1 (1st June 2021) - Kopitz, Linda
Abstract: As millions of customers across the world invite digital voice assistants into their homes, the public debate has increasingly centered on security and privacy concerns connected to the use of the device. Drawing on Tania Bucher's work at the intersection between technology and everyday experience, this article proposes an understanding of an algorithmic imaginary of Alexa-enabled devices as explicitly nonthreatening in its ordinariness, positive potential, and gendered presence. As a case study, this article uses commercials for Alexa-enabled devices as a starting point: Instead of foregrounding the functionality and thereby the algorithmic intelligence underlying the voice assistant, these commercials focus on an affective potential as a narrative strategy to address privacy and security concerns. By connecting everyday interactions with emotional and empowering narratives, the way Alexa is portrayed as an embodied object functions as a balance to the equally public and publicized understanding of digital voice assistants as threats.